2019
DOI: 10.1002/jia2.25417
|View full text |Cite
|
Sign up to set email alerts
|

High HIV prevalence and associated risk factors among transgender women in China: a cross‐sectional survey

Abstract: Introduction Transgender women may face the highest prevalence of HIV of any population, experiencing a disproportionate burden of disease frequently confirmed in surveys throughout the developing and developed world. However, few studies have been conducted specifically for transgender women in China. This study aimed to measure HIV prevalence and explore risk factors for infection in a diverse sample of Chinese transgender women to help advocate for prevention and care interventions for this population. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
(50 reference statements)
2
10
0
1
Order By: Relevance
“…This study revealed an HIV prevalence of 16.5% among TGW in Ho Chi Minh City. This prevalence was higher than the findings from other countries, including Cambodia (5.9%) [19], China (14.8%) [20] and Malaysia (11.7%) [6]. This observed prevalence highlights the high risk for HIV infection among transgender women in Vietnam and was consistent with global literature regarding the high burden of HIV infection among the transgender population [5].…”
Section: Discussionsupporting
confidence: 84%
“…This study revealed an HIV prevalence of 16.5% among TGW in Ho Chi Minh City. This prevalence was higher than the findings from other countries, including Cambodia (5.9%) [19], China (14.8%) [20] and Malaysia (11.7%) [6]. This observed prevalence highlights the high risk for HIV infection among transgender women in Vietnam and was consistent with global literature regarding the high burden of HIV infection among the transgender population [5].…”
Section: Discussionsupporting
confidence: 84%
“…A explicação proposta pelos autores foi: as mulheres transexuais que não desejavam os efeitos feminizadores dos hormônios ou não podiam pagar por ele eram vistas como transgressoras das normas de gênero pelas comunidades trans e cisgênero, tornandose mais vulneráveis, e portanto com maior risco, à infecção por HIV. Outro ponto tratado no estudo é que as mulheres trans que praticam mais sexo não fazem uso de hormônios para não terem a libido diminuída, o que aumenta o risco de infecções sexualmente transmissíveis 47 .…”
Section: Formas Farmacêuticasunclassified
“…However, as transgender women are often hidden and their gender identity data usually could not be collected completely or consistently, current related research is still limited. And despite three studies reporting a prevalence of 7.6%–14.8% among Chinese transgender women [ 2 , 17 , 18 ], they were primarily cross-sectional design, either with small sample size or provide little information on their differences within the broad category “MSM”. It is known that HIV incidence could well reflect HIV epidemic trend as well as the effect of HIV prevention and control efforts.…”
Section: Introductionmentioning
confidence: 99%